Analisis Eektivitas Gaya Kepemimpinan Demokratis Kepala Sekolah dalam Manajemen Konflik di Lingkungan Pendidikan - Musfiroh, Khofifah Aini; Fanani, Ahmad Falasul; Kurniawan, Bima; Amaniyah, Kamilia; Mu' Alimin, Mu' Alimin (Universitas Islam Negeri Walisongo, 2024)
This study aims to analyze the effectiveness of the democratic leadership style of school principals in managing conflic in educational environments, as well as provide an understanding of how school principals develop an effective leadership approach that is in accordance with legal norms and the moral values of society. This research employs a qualitative method, focusing on literature review as the object of study, which involves data collection by searching for and exploring relevant literature related to the formulation of the problem. The results of the study indicate that the democratic leadership style of school principals has a positive impact on managing conflict, by increasing active participation and collaboration in decision making. This leadership style also creates open communication, mutual trust, and shared responsibility that can reduce tension and make conflict a source of ideas and innovation. In addition, democratic leadership style contributes to increased performance, job satisfaction, and creates a positive work atmosphere, which ultimately supports the achievement of educational goals. This study also emphasizes the importance of implementing a democratic approach in increasing teacher and staff involvement and motivation. Suggestions for further researchers are to explore the impact of democratic leadership style on other aspects of school management, and to conduct additional studies to evaluate the effectiveness of democratic leadership in crisis situations. This is important to obtain a more comprehensive picture of its influence on the quality of education, as well as to understand the limitations of the approach.